المقدّرات والإمكانات الطاقية للاقتصاد الروسي الحديث - ديوب محمد; اسماعيل رولا; صادق علا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Currently, energy security is considered as the cornerstone of economic security and hence the overall security and stability of all States. It is able to determine the specific gravity of the State and to shape its relations with other States. This is exactly what happened to the Russian Federation, whose energy discoveries recently, contributed to the quantities that made it the largest incubator of natural gas. This fact has brought Russia back to the international arena after the collapse of the Soviet Union. Russia has a high proportion of energy fuel, which is an important asset that began to invest not long time ago. Natural gas at the top of this wealth, which in turn carried the name of the Russian incubator to the first refineries when talking about alternative energies, followed by oil and coal and up to renewable energies, respectively. This research sheds light on two of these energies (gas and oil) because of the substitution relations in the wheel of the economy because of the discoveries of the first and warning the second near depletion. The study aimed to identify the relative weight of each type of energy as a basis for all other sectors of the Russian national economy. The study used the descriptive analytical approach to describe the variables that will figure the relationship between the energy sector and the rest of the economies in Russia. The study concluded that the energy sector has the largest share in the revenues of the Russian economy, and contributed to maintaining a certain degree of economic stability in Russia in the period of the recent economic crisis, which gave the Russian economy an opportunity to prove its presence in front of the major economies. يعد الأمن الطاقي في وقتنا الراهن عصب الأمن الاقتصادي، ومن ورائه الأمن والاستقرار الشامل للدول برمتها، وهو الأقدر على تحديد الثقل النوعي للدولة ورسم علاقاتها مع الدول الأخرى. وهذا تماما ما حصل لجمهورية روسيا الاتحادية التي أسهمت اكتشافات الطاقة فيها مؤخرا عن كميات جعلتها تصنف الحاضنة الأكبر لبعضها (كالغاز الطبيعي)، الأمر الذي أعادها وبقوة إلى الساحة الدولية بعد أن غيّبها انهيار الاتحاد السوفييتي. يحوز الوقود الطاقي بأنواعه على نسبة مرتفعة من ثروات روسيا ومقدراتها والتي بدأ استثمارها بشكل أمثل منذ مدة ليست ببعيدة، وعلى رأسها الغاز الطبيعي الذي حمل اسم الحاضنة الروسية إلى المصاف الأولى عند الحديث عن الطاقات البديلة، يليه كل من النفط والفحم الحجري وصولا إلى الطاقات المتجددة على التوالي. يسلط هذا البحث الضوء على اثنتين من هذه الطاقات (الغاز والنفط) لما يربطهما من علاقات إحلال في عجلة الاقتصاد بسبب اكتشافات الأولى وإنذار الثانية بالنضوب القريب، حيث هدفت الدراسة إلى الوقوف على الوزن النسبي لكل نوع من أنواع الطاقة كوقود محرك لسائر قطاعات الاقتصاد الوطني الروسي، متبعة المنهج الوصفي لتوصيف المتغيرات التي ستدرس بدورها العلاقة بين قطاع الطاقة وباقي قطاعات الاقتصاد الوطني في روسيا. خلصت الدراسة إلى أن لقطاع الطاقة الحصة الكبرى في عائدات الاقتصاد الروسي، كما أنه أسهم في الإبقاء على حد معين من الاستقرار الاقتصادي في روسيا في فترة الأزمة الاقتصادية الأخيرة، الأمر الذي أعطى فرصة للاقتصاد الروسي بإثبات وجوده أمام الاقتصاديات الكبرى التي خرجت منهكة جراء تلك الأزمة.